Neuroactive Multifunctional Tacrine Congeners with Cholinesterase, Anti-Amyloid Aggregation and Neuroprotective Properties - Maria Kozurkova; Pavol Kristian; Helena Paulikova; Slavka Hamulakova; Zuzana Gazova (MDPI AG, 2011)
The review summarizes research into the highly relevant topics of cholinesterase and amyloid aggregation inhibitors connected to tacrine congeners, both of which are associated with neurogenerative diseases. Various opinions will be discussed regarding the dual binding site inhibitors which are characterized by increased inhibitor potency against acetylcholin/butyrylcholine esterase and amyloid formation. It is suggested that these compounds can both raise levels of acetylcholine by binding to the active site, and also prevent amyloid aggregation. In connection with this problem, the mono/dual binding of the multifunctional derivatives of tacrine, their mode of action and their neuroprotective activities are reported. The influence of low molecular compounds on protein amyloid aggregation, which might be considered as a potential therapeutic strategy in the treatment of Alzheimer's disease is also reported. Finally, attention is paid to some physico-chemical factors, such as desolvation energies describing the transfer of the substrate solvated by water, the metal-chelating properties of biometals reacting with amyloid precursor protein, amyloid beta peptide and tau protein.